Evaluation of Supercritical Extracts of Algae as Biostimulants of Plant Growth in Field Trials - Michalak, Izabela; Chojnacka, Katarzyna; Dmytryk, Agnieszka; Wilk, Radosław; Gramza, Mateusz; Rój, Edward (Frontiers in Plant Science, 2016)
The aim of the field trials was to determine the influence of supercritical algal extracts on the growth and development of winter wheat (variety Akteur). As a raw material for the supercritical fluid extraction (SFE), the biomass of microalga Spirulina plantensis, brown seaweed – Ascophyllum nodosum and Baltic green macroalgae was used. Forthial and Asahi SL constituted the reference products. It was found that the tested biostimulants did not influence statistically significantly the plant height, length of ear and shank length. The ear number per square meter was the highest in the group where the Baltic macroalgae extract was applied in the dose 1.0 L/ha (statistically significant differences). Number of grains in ear (statistically significant differences) and shank length was the highest in the group treated with Spirulina at the dose 1.5 L/ha. In the group with Ascophyllum at the dose 1.0 L/ha, the highest length of ear was observed. The yield was comparable in all the experimental groups (lack of statistically significant differences). Among the tested supercritical extracts, the best results were obtained for Spirulina (1.5 L/ha). The mass of 1000 grains was the highest for extract from Baltic macroalgae and was 3.5% higher than for Asahi, 4.0% higher than for Forthial and 18.5% higher than for the control group (statistically significant differences). Future work is needed to fully characterize the chemical composition of the applied algal extracts. A special attention should be paid to the extracts obtained from Baltic algae because they are inexpensive source of naturally occurring bioactive compounds, which can be used in sustainable agriculture and horticulture.